A comprehensive stepped planing hull systematic series: Part 1 - Resistance test. (15th December 2022) - Vitiello, Luigi; Mancini, Simone; Bilandi, Rasul Niazmand; Dashtimanesh, Abbas; De Luca, Fabio; Nappo, Vincenzo
Abstract: This work addresses the experimental study of a new systematic series of stepped planing hulls. Indeed, the interest in the stepped planing hulls is constantly growing, both in the industrial/commercial and academic fields. Designers and boat builders have been orienting toward the multi-stepped hulls solution to ensure good dynamic stability, reliable seakeeping and operability at high speeds. However, there is a lack of a comprehensive stepped hull systematic series with various step configurations including a forward V-shaped step, as typically used on modern boats. For the abovementioned reasons, a systematic series of eight different models of stepped hulls have been developed and tested. The towing tank tests have been carried out at the naval basin of the Università degli Studi di Napoli "Federico II" Dipartimento di Ingegneria Industriale (DII) in calm water at different speeds ( Fr ∇ = 1.077–6.774) and for three different static trim conditions. All models are built with a transparent bottom to visualize the wetted surface and the eventual development of vortices generated behind the step. The eight models are defined by modifying three significant design parameters for stepped hulls (i.e. the number of steps, longitudinal step position, and step height). Highlights: Calm water towing tank test results of a systematic series of 8 stepped hull models are provided. The hydrodynamics effects by step numbers, longitudinal position of the steps, and the height of the steps are investigated. The models were built in composite materials with a transparent bottom to provide a full view of the water flow under the hull Calm water resistance tests were conducted following the "down-thrust" (DT) methodology with a towed point located on the hull bow.